Sociology of e-social control - Argüello López, Carlos Humberto (2015)
ABSTRACT This essay-paper is a sustainable option to a cyber-democracy; this spotlight is based on the progress of the supercomputer networks being developed, where the citizens can use it for a decision making. The electronic democratization gives a special treatment to improve the structures and systems of democracy that influence the social significance of information substitute and policy deliberations in the framework of civil participatory activities.